Stress levels, hematological condition, and productivity of plasma-producing horses used for snake antivenom manufacture: a comparison of two industrial bleeding methods - Arias Esquivel, Ana Margarita (2024)
The immunization and industrial bleeding of horses are essential stages for producing snake antivenoms. In Costa Rica, the traditional method involves stimulating the antibody response of horses by periodically injecting venoms, collecting hyperimmune plasma over three consecutive bleeding days, and repeating this process every eight weeks. While this method does not cause major physical or hematological issues in horses, the associated stress has not been evaluated. We compared this traditional method with an alternative method that involves injecting venoms, collecting hyperimmune plasma in a single bleeding day, and repeating the process every two weeks. We assessed stress (via serum and fecal cortisol levels and an ethological study), hematological parameters (hematocrit and hemoglobin concentration), and plasma productivity over eight months. Serum cortisol levels remained within the normal range for both methods throughout the immunization/bleeding cycle. However, serum and fecal cortisol levels were significantly higher in horses subjected to the traditional method compared to those in the alternative method. Neither method caused significant hematological alterations. Notably, the alternative method yielded a higher volume of plasma. We concluded that adopting the alternative method ensures horse welfare while improving industrial bleeding productivity. This approach may reduce costs and improve the availability of this essential treatment for vulnerable populations.